2009
DOI: 10.1107/s1744309109023392
|View full text |Cite|
|
Sign up to set email alerts
|

Crystallization and crystallographic analysis of the apo form of the orange protein (ORP) fromDesulfovibrio gigas

Abstract: The orange-coloured protein (ORP) from Desulfovibrio gigas is a 12 kDa protein that contains a novel mixed-metal sulfide cluster of the type [S 2 MoS 2 -CuS 2 MoS 2 ]. Diffracting crystals of the apo form of ORP have been obtained. Data have been collected for the apo form of ORP to 2.25 Å resolution in-house and to beyond 2.0 Å resolution at ESRF, Grenoble. The crystals belonged to a trigonal space group, with unit-cell parameters a = 43, b = 43, c = 106 Å .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 15 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of 3‐NT formation by a Ni II ‐ATCUN in the presence of the NO 2 − /SO 3 2− /O 2 system. For this experiment, we used fusion orange protein (ATCUN‐ORP) as an in vitro model complex containing ATCUN tag at the N‐terminus (ASH) and native Tyr 75 located in cluster binding region of ATCUN‐ORP (Figure ) . Recently, we have reported that cluster formation in ORP occur by protein–protein interaction in head‐to‐tail fashion, in which the N‐terminus metal‐binding ATCUN motif comes to the cluster‐binding region, in which Tyr residues are affected through pseudocontact .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first report of 3‐NT formation by a Ni II ‐ATCUN in the presence of the NO 2 − /SO 3 2− /O 2 system. For this experiment, we used fusion orange protein (ATCUN‐ORP) as an in vitro model complex containing ATCUN tag at the N‐terminus (ASH) and native Tyr 75 located in cluster binding region of ATCUN‐ORP (Figure ) . Recently, we have reported that cluster formation in ORP occur by protein–protein interaction in head‐to‐tail fashion, in which the N‐terminus metal‐binding ATCUN motif comes to the cluster‐binding region, in which Tyr residues are affected through pseudocontact .…”
Section: Figurementioning
confidence: 99%
“…Structures of apo‐ATCUN‐ORP ( D. gigas ) are deduced from PDB file 2wfb, see Ref. . Ni‐ATCUN catalyzed Tyr to 3‐NO 2 ‐Tyr in the presence of Na 2 NO 2 /Na 2 SO 3 /O 2 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In the article by Najmudin et al (2009) the name of one of the authors was given incorrectly: the name Pualeta should be spelt Pauleta. The correct list of authors is S. Najmudin, C. Bonifá cio, A. G. Duarte, S. R. Pauleta, I. Moura, J. J. G. Moura and M. J. Romã o.…”
mentioning
confidence: 99%